The Acute Effects of Non-concussive Head Impacts on Brain Microstructure, Chemistry and Function in Male Soccer Players: A Pilot Randomised Controlled Trial - Nathan Delang; Rebecca V. Robertson; Fernando A. Tinoco Mendoza; Luke A. Henderson; Caroline D. Rae; Stuart J. McDonald; Ben Desbrow; Christopher Irwin; Aimie L. Peek; Elizabeth A. Cairns; Paul J. Austin; Michael A. Green; et al. (Sports Medicine - Open)
Abstract Background Head impacts, particularly, non-concussive impacts, are common in sport. Yet, their effects on the brain remain poorly understood. Here, we investigated the acute effects of non-concussive impacts on brain microstructure, chemistry, and function using magnetic resonance imaging (MRI) and other techniques. Results Fifteen healthy male soccer players participated in a randomised, controlled, crossover pilot trial. The intervention was a non-concussive soccer heading task (‘Heading’) and the control was an equivalent ‘Kicking’ task. Participants underwent MRI scans ~ 45 min post-task which took ~60 min to complete. Blood was also sampled, and cognitive function assessed, pre-, post-, 2.5 h post-, and 24 h post-task. Brain chemistry: Heading increased total N-acetylaspartate (p = 0.012; g = 0.66) and total creatine (p = 0.010; g = 0.77) levels in the primary motor cortex (but not the dorsolateral prefrontal cortex) as assessed via proton magnetic resonance spectroscopy. Glutamate-glutamine, myoinositol, and total choline levels were not significantly altered in either region. Brain structure: Heading had no significant effects on diffusion weighted imaging metrics. However, two blood biomarkers expressed in brain microstructures, glial fibrillary acidic protein and neurofilament light, were elevated 24 h (p = 0.014; g = 0.64) and ~ 7-days (p = 0.046; g = 1.19) post-Heading (vs. Kicking), respectively. Brain Function: Heading decreased tissue conductivity in 11 clusters located in the white matter of the frontal, occipital, temporal and parietal lobes, and cerebellum (p’s < 0.001) as assessed via electrical properties tomography. However, no significant differences were identified in: (1) connectivity within major brain networks as assessed via resting-state functional MRI; (2) cerebral blood flow as assessed via pseudo continuous arterial spin labelling; (3) activity within electroencephalography frequencies (infra-slow [0.03–0.06 Hz], theta [4–8 Hz], alpha [9–12 Hz], or beta [13–25 Hz]); or (4) cognitive (memory) function. Conclusions This study identified chemical, microstructural and functional brain alterations in response to an acute non-concussive soccer heading task. These alterations appear to be subtle, with some only detected in specific regions, and no corresponding cognitive deficits observed. Nevertheless, our findings suggest that individuals should exercise caution when performing repeated non-concussive head impacts in sport. Trial registration ACTRN12621001355864. Date of registration: 7/10/2021. URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382590&isReview=true .